Understanding the potential of PARO for healthy older adults. Issue 100 (April 2017) - McGlynn, Sean A.; Kemple, Shawn; Mitzner, Tracy L.; King, Chih-Hung Aaron; Rogers, Wendy A.
Abstract: As the population ages, there is an increasing need for socio-emotional support for older adults. A potential way to meet this need is through interacting with pet-type robots such as the seal robot, PARO. There was a need to extend research on PARO's potential benefits beyond cognitively impaired and dependently living older adults. Because independently living, cognitively intact older adults may also have socio-emotional needs, the primary goal of this study was to investigate their attitudes, emotions, and engagement with PARO to identify its potential applicability to this demographic. Thirty older adults participated in an interaction period with PARO, and their attitudes and emotions toward PARO were assessed before and after using a multi-method approach. Video of the interaction was coded to determine the types and frequency of engagements participants initiated with PARO. Overall, there were no pre-post interaction differences on these measures. However, semi-structured interviews suggested that these older adults had positive attitudes towards PARO's attributes, thought it would be easy to use, and perceived potential uses for both themselves and others. Participants varied in their frequency of engagement with PARO. A novel finding is that this active engagement frequency uniquely predicted post-interaction period positive affect. This study advances understanding of healthy older adults' attitudes, emotions, and engagement with PARO and of possible ways in which PARO could provide social and emotional support to healthy older adults. The results are informative for future research and design of pet-type robots. Highlights: Healthy older adults had generally positive attitudes toward PARO. Healthy older adults were neutral regarding PARO's usefulness. Healthy older adults thought PARO would be easy to use. Engagement type & frequency when interacting with PARO varied between participants. Engagement frequency uniquely predicted post-interaction positive affect.